2013
DOI: 10.1111/ggi.12161
|View full text |Cite
|
Sign up to set email alerts
|

Is the Cambridge Cognitive Examination - Revised a good tool for detection of dementia in illiterate Brazilian older adults?

Abstract: The Br-CAMCOG-R was useful for identifying cases of dementia among older adults with middle and low levels of literacy, but inadequate for the illiterate individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Complaints were evaluated in detail by the geriatricians in order to define the presence or absence of major depression or dysthymia. Assessment of cognitive level was carried out with the MMSE (Folstein et al, 1975;Lourenço and Veras, 2006) and with the Informant Questionnaire on Cognitive Decline in the Elderly (Roth et al, 1998;Paradela and Lourenço, 2014). The diagnosis of dementia syndrome was conducted by consensus among geriatricians and neuropsychologists according to the criteria of Diagnostic and Statistical Manual of Mental Disorder-Fourth Edition.…”
Section: Participants and Settingmentioning
confidence: 99%
“…Complaints were evaluated in detail by the geriatricians in order to define the presence or absence of major depression or dysthymia. Assessment of cognitive level was carried out with the MMSE (Folstein et al, 1975;Lourenço and Veras, 2006) and with the Informant Questionnaire on Cognitive Decline in the Elderly (Roth et al, 1998;Paradela and Lourenço, 2014). The diagnosis of dementia syndrome was conducted by consensus among geriatricians and neuropsychologists according to the criteria of Diagnostic and Statistical Manual of Mental Disorder-Fourth Edition.…”
Section: Participants and Settingmentioning
confidence: 99%
“…Aprahamian et al described sensitivities/specificities of 88.1%/83.5%, and 84.6%/96% in subjects with 1‐4 y/5‐8 y of education, respectively, as regarding the accuracy of the original CAMCog in discriminating controls from patients with Alzheimer disease. Paradela and Lourenço reported these sensitivities and specificities to be 83%/85% for low (1‐4 y) educational level and 90%/76% for middle (5‐8 y) educational level when using the CAMCog‐R. The study by Aprahamian et al reported a sensitivity and specificity of 70.8% and 90% for controls/AD discrimination in highly educated (≥9 y) subjects.…”
Section: Discussionmentioning
confidence: 53%
“…In addition, scores may still depend on the years of education, as evidenced by the high rates of errors in the items involving reading and writing abilities, in the Cambridge Cognition Examination 20 . Consequently, the proposed adaptations may not be entirely suitable for the illiterate population 3,45,46,47 .…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the reviewed studies highlight that social and cultural factors should be taken into account when interpreting cognitive screening results, and that screening approaches should overcome the impact of educational and sociocultural heterogeneity on cognition 21,41,45,58 , either by the adjustment of cut-off scores or appropriate test construction or adaptation 59,60 .…”
Section: Discussionmentioning
confidence: 99%